Penerapan Daily Physical Activity di Sekolah Malacampa Elementary School-Main, Tarlac City, Philippines - Utami, Nissa Aulia Belistiana; Situmorang, Andi Suntoda; Slamet, Suherman (TEGAR: Journal of Teaching Physical Education in Elementary School, 2020)
The education system in the Philippines has changed because it refers to the United Nations program, the Sustainable Development Goals. One of the changes is that each student is required to attend the Daily Physical Activity program before starting learning. This research is conducted at Malacampa Elementary School-Main, Tarlac City, Philippines. The purpose of this study is to determine what impacts occur after the implementation of the Daily Physical Activity which is carried out every morning in the long run. Daily Physical Activity is done by dancing 10 to 15 minutes. This type of research is an ex-post-facto study in which the researcher examines a program that is happening in the Philippines. Researchers take samples of one class, named class 6 SSES, amounting to 27 students. Based on the results of this study, there are positive impacts in the form of children being more enthusiastic in doing daily tasks and negative in the form of students feeling bored with less varied songs and movements.AbstrakSistem Pendidikan di Filipina berubah karena merujuk program PBB yaitu Sustainable Development Goals. Salah satu perubahannya yaitu setiap siswa wajib mengikuti program Daily Physical Activity sebelum memulai pembelajaran. Penelitian ini merupakan penelitian yang dilakukan di Malacampa Elementary School-Main, Tarlac City, Philippines. Tujuan dari penelitian ini yaitu untuk mengetahui dampak apa saja yang terjadi setelah diterapkannya Daily Physical Activity yang dilakukan setiap pagi hari dalam jangka waktu yang panjang. Daily Physical Activity yang dilakukan adalah menari 10 sampai 15 menit. Jenis penelitian ini merupakan penelitian ex-post facto di mana peneliti meneliti program yang sedang terjadi di Filipina. Peneliti mengambil sampel satu kelas, yaitu kelas 6 SSES yang berjumlah 27 siswa. Berdasarkan hasil penelitian ini yaitu adanya dampak positif berupa anak lebih antusias dalam melakukan tugas gerak di kesehariannya dan negatif berupa siswa merasa bosan dengan lagu dan gerakan yang kurang bervariatif.